1977
DOI: 10.1159/000117596
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Rubidium in the Organism

Abstract: After the intraperitoneal administration of 86RbCl to mice in a dose of 0.5 mM/kg, the maximum levels in the liver and kidneys were attained in the first hour, but in the brain not for 24 h. The Rb+ half-time in the tissues was about 170 h. With peroral administration, tissue rubidium levels at 3 days were higher than after intraperitoneal injec-tion. Rubidium did not affect sodium levels in rats, but lowered potassium levels. Cesium led to an increase in tissue rubidium levels, while diu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
(7 reference statements)
1
3
0
Order By: Relevance
“…The release of rubidium from the cell depends on diffusion, which is very slow; this explains the considerable biological half-times for this ion, as seen from our own study (8) and from the works of other authors (3,4). It must further be emphasized, however, that affinity of the cell proteins can also play a very important role in maintenance of the intracellular rubidium concentration.…”
Section: Discussionsupporting
confidence: 58%
“…The release of rubidium from the cell depends on diffusion, which is very slow; this explains the considerable biological half-times for this ion, as seen from our own study (8) and from the works of other authors (3,4). It must further be emphasized, however, that affinity of the cell proteins can also play a very important role in maintenance of the intracellular rubidium concentration.…”
Section: Discussionsupporting
confidence: 58%
“…We have shown that cesium transport differs somewhat from potassium and rubidium transport (9). In this, passive transport probably plays an important role and active transport across the cell membrane may also be different from that of rubidium.…”
Section: Discussionmentioning
confidence: 75%
“…rubidium, it is not localized strictly intracellularly and its infiltration into the cell takes much longer. The plasma and RBC rubidium levels were found to even out in 1.5 h in rats and in 4 h in man (9). The time for cesium is significantly longer -about 7 h in rats and dozens of hours in man.…”
Section: Discussionmentioning
confidence: 91%
“…It has also been found that rubidium and manganese, in addition to zinc, are preferentially taken up by tumors in the brain . It could replace potassium in the Na + K‐ATPase (sodium‐potassium pump) system . Rubidium chloride might have application in future psychochemical research and therapy of the affective disorders such as depressions .…”
Section: Resultsmentioning
confidence: 99%